Princess Daisy and the dazzling dragon - French, Vivian; Gibb, Sarah (New York : Orchard Books, 2005)
A timid young princess is afraid of dragons until she sees one for herself, then has the opportunity to prove her newfound courage to the entire school.
H
b
b
Keywords: Princesses -- Fiction; Courage -- Fiction; Dragons -- Fiction; Schools -- Fiction